Pioneering a New Approach to Improving Working Conditions in Developing Countries: Better Factories Cambodia - Raymond Robertson (Institute of Labor Economics (IZA), 2020)
The rise of global supply chains over the last three decades intensified international attention to the conditions endured by workers in poor countries. Collapsed buildings, fires and death created an imperative to address poor conditions. Consumers, non-governmental organizations, inter-governmental organizations, international buyers and governments began seeking ways to improve working conditions in exporting factories in developing countries. The goals of this chapter is to describe the birth and growth of the Better Factories Cambodia (BFC) program, review the academic literature that has focused on both the BFC program and its descendent, Better Work, and identify some of the key aspects of the program that have been shown to be particularly successful.
Keywords: F16; F66; F23; J8; 330; working conditions; global value chains; Cambodia; Better Factories Cambodia